Institut Agama Islam Imam Al-Ghazali Cilacap - Zulfa, Umi (Nadwa, 2013)
This study aims to find a new PAI learning model that is more creative and innovative. Data collection methods used were observation, interview and documentation. The data analysis technique used was the qualitative analy-sis of interactive models. Based on the research methods used, the findings are: a) the policy of the PAI learning in SDIP Kroya deals with learning inside and outside the classroom, b) the implementation stages of the PAI learning are through religious values socialization, religious values inter-nalization, continuity and religious values institutionalization, c) learning outcomes indicate that the new religious values just become a custom made by students, not as strong character, d) the PAI learning model found with the name of SICI learning Model.